A question of trust: post-truth paradigms and the challenge to financial regulation. Issue 1 (2nd January 2017) - O'Brien, Justin
Abstract : Trust in institutions is falling at an alarming rate, the cause and consequence of democratic rejection of strategies to deal with the Global Financial Crisis. Irrespective of whether rule- or principles-based forms of regulation were privileged, each failed to address the erosion of core normative anchors. Blindsided by the factors that led to the crisis, the policy response, based largely on technical solutions, has done little to restore trust. As will be shown, it further eroded it. The result is an existential crisis for the liberal state and the international regulatory order. Rebuilding trust requires substantial refashioning of purpose buttressed by change in the role and function of industry codes of conduct. Without anchoring commitment to broader social purpose, these codes risk exacerbating the distrust they are ostensibly designed to ameliorate. This article explores these dynamics through an extended analysis of proposed changes to the Australian Bankers' Association Code of Conduct. It argues that, despite rhetorical commitment to a social licence to operate, the lack of an explicit normative dimension undermines authority and legitimacy.